EVALUATING ONLINE DISCUSSIONS: FOUR DIFFERENT FRAMES OF ANALYSIS - Meyer, Katrina A. (Online Learning, 2004)
This study uses four different “frames” to analyze 17 online discussions that occurred in two doctoral level classes in educational leadership. Two of the frames were developmental models: King and Kitchener’s Reflective Judgment Model and Perry’s model of intellectual and ethical development. Two of the frames captured levels of thinking: Garrison’s four-stage critical-thinking model and Bloom’s taxonomy of educational objectives. Of the 278 individual postings, 45.3% were at levels five through seven of the King and Kitchener model, 100% were at levels five through nine of the Perry model, 52.2% were at the two highest levels of the Garrison model, and 54.3% were at levels four through six in Bloom’s taxonomy. These results seem appropriate to the level of response expected of doctoral students. For each frame, the analysis resulted in additional findings. The study concludes that each frame has value and focuses attention on different aspects of the student’s thinking as evidenced in his/her posting to an online discussion; however, some frames are more difficult to use than others, which argues for specific training and/or tailoring the topic of discussions to address issues in a particular manner. Lastly, the question initiating each of the online discussions influenced the level of the responses from students. Each frame has the potential to illumine students’ online discussions, although using multiple frames may have more benefit than using any one frame exclusively.